Business Design and Feasibility Analysis of Barbercome Startup - Esti Retno Listiyani; Maria Dellarosawati Idawicaksakti; Tiara Verita Yastica (JTI: Jurnal Teknik Industri, 2024)
Barbercome is a startup in the hair care industry, founded in 2023. Barbercome is a mobile application that accommodates barbershops and barbers, allowing users to order home-based haircut services and make barbershop queue reservations. This application is a solution for customers who are often busy with their daily activities, have a busy work schedule, and lack free time to go to the barbershop. Many customers postpone or skip hair treatments due to inconveniences such as cuts that are not as expected, prices that are not commensurate with the quality of service, long waiting times even though they have made an appointment in advance, rushed or unfriendly service, unclean or too crowded barbershop conditions, and barber skills in handling certain types of hair are lacking. As a new business, Barbecome needs to conduct a feasibility analysis to determine whether it is feasible to run or not. The location of this business is in Bandung City. Based on the financial feasibility calculation results, the NPV value was obtained for IDR 75,547,341, PBP of 2.7, and IRR of 28.96%. Based on the feasibility and sensitivity calculations results, it can be concluded that the Barbercome startup business design is feasible to run.  Keywords: Barbercome, Feasibility Analysis, NPV, PBP, IRR